Conservation Nursing Strategies (*)An exploratory study of a sample of managers in Baghdad health departments - قاسم غسان; جواد هند فؤاد (Journal of Economics and Administrative Sciences, 2009)
The deficiency in the nurse staff in the health organizations consider an important problem that must be studied and solved basically , not only because it affect on the health organization and it’s strategic goals , but also it affect the human being and it’s health which can’t be substituted with anything or delayed in it’s treatment ,This research aims to necessary for health organizations to strategically help in maintaining the nurse staff and to keep that in it’s strategic orientation and it’s mission , moreover , the health organizations must study the reality of the nurse in the health organizations and know the causes beyond leaving the nurse staff the nurse job , and then remove these causes from the reality of the nurse in the health organizations to reach finally to the strategies that maintain the nurse staff .The sample of research were (23) managers in hospitals and health centers of Baghdad city to diagnosis strategies of maintaining the nurse staff ,a group of conclusions are determined the most important are limited of strategies follow for these purposes